Pengembangan Sistem Informasi Monitoring Prospek Marketing Menggunakan Framework Laravel (Studi Kasus: PT Asuransi Bintang Tbk Cabang Lampung) - Rahman Taufik; Syahril Fajri Pratama; Muhaqiqin Muhaqiqin; Ridho Sholehurrohman; Igit Sabda Ilman (Jurnal Pepadun, 2023)
Insurance companies exist as a means to protect individuals or businesses from unexpected financial risks, such as losses resulting from accidents, natural disasters, fires, or theft. Monitoring the marketing prospect reporting is one of the challenges faced by every insurance company. In light of this issue, this research proposes the development of a marketing prospect monitoring information system. The development of this information system uses Laravel Framework and employs a prototype method, encompassing stages of requirement gathering, design, implementation, evaluation, and system distribution. The results show that this information system has a positive contribution to the company and addresses previous issues, although there are some improvements that need to be considered in the future.